Effect of water temperature on the anesthetic effects of alfaxalone in carp (Cyprinus carpio) - Maeda, Kenichi; Hotta, Daiki; Matsui, Takuma; Iwai, Satomi; Okanao, Shozo (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: To evaluate the effect of water temperature on intramuscular injected alfaxalone anesthesia in carp (Cyprinus carpio). Materials and Methods: Six healthy adult carp (C. carpio) were intramuscularly injected with alfaxalone (2.5, 5.0, or 7.5 mg/kg) at normal water temperature (25°C) and at low water temperature (2.5 mg/kg, 15°C). The respiratory rate, heart rate (HR), and anesthesia depth (AD) were evaluated every 5 min for 30 min after administration and every 1 h after 60 min after injection. Results: The respiratory and HRs did not change significantly upon alfaxalone injection, regardless of dose. However, a dose-dependent increase in AD scores was observed. Furthermore, 2.5 mg/ kg alfaxalone injected in 15°C water showed an almost equal anesthetic effect to that of 5.0 mg/ kg alfaxalone in 25°C water. Conclusion: Alfaxalone is readily available, and its anesthetic effect in carp was enhanced by lowering water temperature, illustrating the possibility of intramuscular injection of alfaxalone in fish. Adv. Vet. Anim. Res., 11(1): 27-32, March 2024 http://doi.org/10.5455/javar.2024.k743